Efficacy of perioperatively application of ketamine on postoperative depressive symptoms in adult patients: A systematic review and meta-analysis with trial sequential analysis - Wei, Qingfeng; Li, Mengmeng; Jiang, Yu; Liu, Xuesheng (Journal of affective disorders, 2024)
Whether ketamine used in the perioperative period reduces the risk of postoperative depressive symptoms remains uncertain. We conducted this systematic review and meta-analysis to evaluate the clinical efficacy of ketamine in adult surgical patients. Two investigators independently systematically searched the Cochrane Central Register of Controlled Trials (CENTRAL), Medline, Web of Science, and PsycINFO databases using a combination of relevant Medical Subject Headings terms and free-text keywords from database inception through May 24, 2023. 29 studies encompassing 5327 patients were included. The pooled analysis demonstrated that the ketamine group had no significantly reduced incidence of postoperative depressive mood compared with the control group, with trial sequential analysis (TSA) inconclusive. However, postoperative depression scale scores were significantly decreased in the ketamine group. Most randomized controlled trials of surgical patients have included depression scale scores as the primary outcome. The incidence of postoperative depressive has been assessed as a secondary outcome or has not been assessed. In addition, non-uniform assessment scales have introduced greater heterogeneity. More rigorous methods and higher-quality evidence for further research are needed to better understand the effects of ketamine on perioperative depression in surgical anesthesia. Current evidence suggests that ketamine cannot significantly decrease the incidence of postoperative depressive mood in adult surgical patients. However, ketamine can reduce postoperative depression scores. PROSPERO registration: CRD42023431566. •Ketamine does not significantly reduce the incidence of postoperative depressive mood in adult surgical patients.•Perioperative application of ketamine reduces postoperative depressive symptom scores.•Questions like ideal dosing and timing of intervention remain open.